Challenges and Opportunities for Character Education in the Digital Era - Anita Candra Dewi; Putri Fatimah Az-Zahra; Nirwana; Nur ilmi; Nurtin Dwi Putri; Pety Desvita Sari (MultiTech Publisher, 2023)
The purpose of this article is to discuss the challenges and opportunities of character education in the digital age. Building character in the digital age presents many different challenges and opportunities. Research shows that the digital age offers positive opportunities for implementing character education. Our challenge is how to teach students to navigate ethics in the digital age. Some of the challenges faced in character education in the digital age include balance, safety and security, cyberbullying, sexting, copyright, and plagiarism. Education policy makers should play an active role in the continuous development of digital learning to ensure effective implementation of digital learning.